Regulation of HA14‐1 mediated oxidative stress, toxic response, and autophagy by curcumin to enhance apoptotic activity in human embryonic kidney cells. (5th April 2013) - Ranjan, Kishu; Sharma, Anupama; Surolia, Avadhesha; Pathak, Chandramani
<x xml:space="preserve">Abstract</x> An alteration in susceptibility to apoptosis not only contributes to promotion of malignancy but can also enhance drug resistance in response to anticancer therapies. HA14‐1 is a small molecule which has the potential of inducing apoptosis in cancerous cells. HA14‐1 manifests an antagonistic effect on antiapoptotic protein Bcl‐2 and consequently induces cell death in various cancerous cell lines. However, it is also known to generate ROS and toxic response in the cells upon decomposition. Elevated level of ROS is responsible for oxidative stress and other pathological consequences, if not metabolized properly. The aim of the present study was to examine the synergistic effect of curcumin in promoting apoptosis by regulating the HA14‐1 mediated ROS generation, toxicity, oxidative stress, and autophagy in human embryonic kidney cells. Our study demonstrates that curcumin efficiently scavenges HA14‐1 mediated generation of ROS and toxic response resulting in augmentation of apoptosis in HEK 293T cells by promoting inhibition of antiapoptotic proteins and process of autophagy. Thus curcumin along with HA14‐1 regulates cell proliferation by disruption of the antiapoptotic signaling mechanism. This approach could serve as a promising strategy for therapeutic potential to overcome their adverse effects. © 2013 BioFactors, 40(1):157–169, 2014